Pioneers of a peaceable kingdom : the quaker peace testimony from the colonial era to the first World War - Brock, Peter, 1920-2006 (Princeton legacy library., 1968)
Extracted from Pacifism in the United States, this work focuses on the significant contribution of the Quakers to the history of pacifism in the United States. Originally published in 1971. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich schol.